2016
DOI: 10.1108/mf-02-2015-0053
|View full text |Cite
|
Sign up to set email alerts
|

Half a century of research on Value Line: a comprehensive review

Abstract: Purpose – The purpose of this paper is to present a comprehensive review of literature on Value Line. First, the authors summarize the literature examining the Value Line enigma. Second, the authors survey the literature on Value Line’s other valuation metrics. Finally, literature comparing Value Line’s database to other tradition data sources is presented. Design/methodology/approach – Approximately 60 academic articles published from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…Moreover, far too little attention has been paid to modelling uncertainty inherently present in the knowledge of financial analysts and auditors. Indeed, earlier research has shown that expert forecasts significantly outperform traditional statistical models regarding consistency and prediction accuracy [3]. When combined with data analytics methods, expert knowledge was utilized to detect the most serious financial statement frauds [4] and improve the effectiveness of financial audits [5].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, far too little attention has been paid to modelling uncertainty inherently present in the knowledge of financial analysts and auditors. Indeed, earlier research has shown that expert forecasts significantly outperform traditional statistical models regarding consistency and prediction accuracy [3]. When combined with data analytics methods, expert knowledge was utilized to detect the most serious financial statement frauds [4] and improve the effectiveness of financial audits [5].…”
Section: Introductionmentioning
confidence: 99%